Portable 4-Channel Electrochemical Noise Test System - 李健 孔伟康 郑焕军 张力 毛雪伟 (Transactions of Tianjin University, 2014)
A portable 4-channel electrochemical noise（EN） test system with high precision was developed.The modular instrument cRIO was used as its core and the signal conditioning module included zero resistance ammeter（ZRA）,fly line,screening box and shielded wire.The EN data were acquired from two Q235 carbon steel specimens placed in 0.5 mol/L H2SO4 solution and 0.1 mol/L NaCl solution.The experimental result shows that this system can achieve an accuracy of 10 pA and 10 μV,and it can be applied to on-site multi-channel EN test.